Search for dark matter produced in association with a hadronically decaying vector boson in pp collisions at √s=13TeV with the ATLAS detector - Alconada Verzini, María Josefina (2016)
A search is presented for dark matter produced in association with a hadronically decaying W or Z boson using 3.2fb−1 of pp collisions at √s=13TeV recorded by the ATLAS detector at the Large Hadron Collider. Events with a hadronic jet compatible with a W or Z boson and with large missing transverse momentum are analysed. The data are consistent with the Standard Model predictions and are interpreted in terms of both an effective field theory and a simplified model containing dark matter.